2002
DOI: 10.1614/0890-037x(2002)016[0520:ursiaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Using Reflectance Sensors in Agronomy and Weed Science1

Abstract: Weed-detecting reflectance sensors were modified to allow selective interrogation of the near infrared–red ratio to estimate differences in plant biomass. Sampling was programmed to correspond to the forward movement of the field of view of the sensors. There was a linear relationship (r 2 > 0.80) between actual biomass and crop canopy analyzer (CCA) values up to 2,000 kg/ha for winter wheat sequentially thinned to create different amounts of biomass and up to 1,000 kg/ha for spring wheat sampled at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…Other techniques are based on the use of object segmentation algorithms and on the construction of a hierarchical network of image objects, and works on the treatment of several data types simultaneously such as pixel values, object features and hierarchical relationships (Baatz and Schäpe, 1999). Felton et al (2002), and Thorp and Tian (2004) reviewed the uses of remote sensing in agriculture, and reported that, to date, the majority of studies on discriminating plant species in cultivation systems have involved discrete broadband remote sensing using multispectral sensors. Spectral reflectance differences can be enhanced by using vegetation indices, which are mathematical (ratios or linear) combinations between bands or selected wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques are based on the use of object segmentation algorithms and on the construction of a hierarchical network of image objects, and works on the treatment of several data types simultaneously such as pixel values, object features and hierarchical relationships (Baatz and Schäpe, 1999). Felton et al (2002), and Thorp and Tian (2004) reviewed the uses of remote sensing in agriculture, and reported that, to date, the majority of studies on discriminating plant species in cultivation systems have involved discrete broadband remote sensing using multispectral sensors. Spectral reflectance differences can be enhanced by using vegetation indices, which are mathematical (ratios or linear) combinations between bands or selected wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing of weed canopies could be more efficient than field measurements, thus the interest in using this technology for developing weed distribution maps has increased in recent years. The importance of remote sensing in site‐specific agriculture has been widely reviewed by Lamb and Brown (2001), Felton et al. (2002), Radhakrishnan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus interest in using this technology for developing weed distribution maps has increased in recent years. The importance of remote sensing in site‐specific agriculture has been widely reviewed by Felton et al. (2002) and Radhakrishnan et al.…”
Section: Introductionmentioning
confidence: 99%